Think twice - Coben, Harlan, 1962- (Coben, Harlan, 1962- Myron Bolitar novel, 2024)
"A man presumed dead is suddenly wanted for murder in this thriller of secrets, lies, and dangerous conspiracies that threaten to cover up the truth ... Three years ago, sports agent Myron Bolitar gave a eulogy at the funeral of his client, renowned basketball coach Greg Downing. Myron and Greg had history: initially as deeply personal rivals, and later as unexpected business associates. Myron made peace and moved on--until now, when two federal agents walked into his office, demanding to know where Greg Downing is. According to the agents, Greg is still alive--and has been placed at the scene of a double homicide, making him their main suspect. Shocked. Myron needs answers. Myron and Win, longtime friends and colleagues, set out to find the truth, but the more they discover about Greg, the more dangerous their world becomes"--